Effect of different types of ethylene scavengers used in different combinations, on the post-harvest quality and phytochemicals retention of tomatoes (Solanum lycopersicum L.) - Muhammad Zakriya; Ashiq Hussain; Amer Ali Mahdi; Farhat Yasmeen; Tusneem Kausar; Abdul Rehman; Shazia Yaqub; Pinky Fatima; Saima Noreen; Khurram Kabir; Rizwan Nisar; Faiza Iftikhar Gorsi; et al. (Chemical and Biological Technologies in Agriculture, 2023)
Abstract Background Ripening of climacteric vegetable, tomato, is a complicated process that results in numerous physiological and biochemical changes, and role of ethylene in this phenomenon is very crucial. Use of different ethylene scavengers can control the post-harvest ripening and quality of tomatoes. In current study, combinations of chemicals as 2% CaCl2 and KMnO4 (T1), 1 mM salicylic acid and KMnO4 (T2), 2% CaCl2 and K2Cr2O7 (T3) and 1 mM salicylic acid and K2Cr2O7 (T4), were tested to study their effect on pH, acidity, total soluble solids (TSS), vitamin C, lycopene, phenolics, flavonoids and antioxidant activity of treated tomatoes, after 30 and 40 days of storage. Results Weight loss and titratable acidity were significantly reduced in treated tomatoes, even after 40 days, which were high in untreated tomatoes. Total phenolic contents (TPC), total flavonoid contents (TFC) and vitamin C, were significantly lesser in untreated tomatoes after 30 and 40 days of storage, but use of ethylene scavengers caused increment in these phytochemicals during post-harvest storage, with more prominent results of T1. Highest lycopene was found in T0 (9.76 ± 0.2 mg/100 g), due to fully ripened and spoiled tomatoes, as compared to treated samples, while the lowest value was found in T1 (4.82 ± 0.20 mg/100 g). Highest antioxidant activity was detected in T1 (33.80 ± 0.52%), whereas the lowest antioxidant activity was noticed in T0 (22.00 ± 0.2%). Conclusion Findings revealed that during the storage period, the 50 g KMnO4 sachet + 2% CaCl2 exerted most superior effects than the other treatments, and extended the shelf-life of tomato fruits for up to 40 days, with no quality and phytochemicals deterioration. Therefore, tomatoes could be harvested at breaker stage, to optimize the ripening process during storage, through application of ethylene scavengers. Graphical abstract